Asparagus racemosus root-derived carbon nanodots as a nano-probe for biomedical applications - Naik G.G.; Minocha T.; Verma A.; Yadav S.K.; Saha S.; Agrawal A.K.; Singh S.; Sahu A.N. (My University, 2025)
Nowadays, green nanotechnology has emerged as a crucial and eco-friendly approach to combat the problems affecting human health or the environment. It deals with the extensive utilization of plants owing to their cocktail of natural and chemical substances to eliminate adverse pollutants involved in the synthesis of nanomaterials. Herein, we report a facile one-step hydrothermal carbonization approach synthesizing fluorescent bluish-green carbon nanodots (CNDs) using Asparagus racemosus roots termed ARCD. The fluorescence quantum yield of ARCD was further improved by surface passivating it with a 1:1 ratio of Carrageenan (CAR) and Polyethylenimine (PEI), termed ARCCD. First, we demonstrate the application of ARCD and ARCCD as a nano-probe for sensing As3+ and Ag+. Second, we show an inhibitory effect on cancer cell proliferation against breast (MDA-MB-231) and cervical (SiHa) cancer. Also, no significant cytotoxicity was observed in the normal kidney (HEK 293) cells, indicating cytotoxic specificity of the developed CNDs. Third, we demonstrate antibacterial activity against clinically isolated multi-drug-resistant strains and free radicals scavenging potential. Next, we present the in vivo toxicity evaluation of these CNDs in Swiss albino mice, which exhibited minimal toxicity as confirmed by biochemical, hematological, and histological parameters. This study deals with an innovative approach to constructing a multifunctional nano-probe for potential biomedical and environmental applications. Graphical abstract: [Figure not available: see fulltext.]. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.